This woman's work - Delporte, Julie; Jensen, Aleshia; Dascher, Helge, 1965-; Small Press Expo Collection (Library of Congress) ([S.l.] : Drawn & Quarterly, 2019)
"This Woman's Work is a powerfully raw autobiographical work that asks vital questions about femininity and the assumptions we make about gender. Julie Delporte examines cultural artifacts and sometimes traumatic memories through the lens of the woman she is today-a feminist who understands the reality of the women around her, how experiencing rape culture and sexual abuse is almost synonymous with being a woman, and the struggle of reconciling one's feminist beliefs with the desire to be loved. She sometimes resents being a woman and would rather be anything but. Told through beautifully evocative colored pencil drawings and sparse but compelling prose, This Woman's Work documents Delporte's memories and cultural consumption through journal-like entries that represent her struggles with femininity and womanhood. She structures these moments in a nonlinear fashion, presenting each one as a snapshot of a place and time-trips abroad, the moment you realize a relationship is over, and a traumatizing childhood event of sexual abuse that haunts her to this day. While This Woman's Work is deeply personal, it is also a reflection of the conversations that women have with themselves when trying to carve out their feminist identity. Delporte's search for answers in the turmoil created by gender assumptions is profoundly resonant in the era of #MeToo."--
boek
Keywords: Delporte, Julie -- Comic books, strips, etc; Feminism -- Comic books, strips, etc; Graphic novels; Feminism; Comic books, strips, etc; Nonfiction comics; Graphic novels; Nonfiction comics; Comics (Graphic works)